Improving The Methodology of Teaching Fine Arts Through Collaborative Technology (On The Example of Grades 5-6) - Sulaymanova Mukhiba Boltaevna (Researchparks Publishing, 2026)
This article analyzes the theoretical and practical aspects of using collaborative technology in teaching fine arts. Collaborative teaching methods are considered as an important pedagogical tool for activating students' creative activity, developing teamwork skills, and interactively organizing the lesson process. The article highlights the possibilities of collaborative technology in fine art classes, its impact on the formation of students' visual thinking and aesthetic taste. It also substantiates ways to improve teaching methodology using this technology.